2021
DOI: 10.1096/fj.202001660rr
|View full text |Cite
|
Sign up to set email alerts
|

The “Matrisome” reveals the characterization of skin keloid microenvironment

Abstract: Keloids are fibroproliferative dermal tumors of unknown origin that are characterized by the overabundant accumulation of extracellular matrix (ECM) components. The mechanism of keloid formation has remained unclear because of a poor understanding of its molecular basis. In this study, the dermal ECM components of keloids were identified and the pathological features of keloid formation were characterized using large-scale quantitative proteomic analyses of decellularized keloid biomatrix scaffolds. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…When our results on mouse skin are compared to the recent reports describing the matrisome of the healthy human skin dermal compartment (Supplementary Table 5), comparable total numbers of matrisome proteins were detected with a similar enzymatic decellularization method using PLA2 (274 in human when the results of two studies are combined [28,31]). The chemical decellularization method was also used to analyze human dermal samples [30] and led to the identification of less matrisome proteins (99 annotated human matrisome proteins, Supplementary Table 5) but only the NaCl and GuHCl extracts were analyzed and different criteria to define ECM proteins were used, explaining the relatively low number of associated matrisome components found in this list.…”
Section: The Matrisome Of Healthy Adult Mouse Skin Comprises 95 Core Matrisome Proteins and 141 Associated Matrisome Proteinssupporting
confidence: 68%
See 1 more Smart Citation
“…When our results on mouse skin are compared to the recent reports describing the matrisome of the healthy human skin dermal compartment (Supplementary Table 5), comparable total numbers of matrisome proteins were detected with a similar enzymatic decellularization method using PLA2 (274 in human when the results of two studies are combined [28,31]). The chemical decellularization method was also used to analyze human dermal samples [30] and led to the identification of less matrisome proteins (99 annotated human matrisome proteins, Supplementary Table 5) but only the NaCl and GuHCl extracts were analyzed and different criteria to define ECM proteins were used, explaining the relatively low number of associated matrisome components found in this list.…”
Section: The Matrisome Of Healthy Adult Mouse Skin Comprises 95 Core Matrisome Proteins and 141 Associated Matrisome Proteinssupporting
confidence: 68%
“…Finally, protocols based on tissue decellularization, using detergents [26,27] or enzymes such as phospholipase A2 (PLA2) [28], which were initially developed for the analysis of the ECM from cardiovascular tissues or the production of acellular scaffolds [29], also proved efficient to enrich matrisome proteins and facilitate their identification by tandem mass spectrometry (MS/MS). These decellularization protocols were recently applied to human skin and led to the identification of between 137 and 267 ECM proteins [28,30,31]. However, when applied to rat skin, the PLA2 decellularization approach only yielded 102 matrisome proteins [28], suggesting that it may not be optimal to analyze murine skin.…”
Section: Introductionmentioning
confidence: 99%
“…Ossification and fibrosis-related glycoproteins and inflammation and aging-related regulators were enriched in elderly skin. In our recently work (Zhang et al, 2021), the dermal ECM components of keloids tissues have been identified. By comparing the data with the keloids ECMs, we found some of the components, e.g., SLPI, THBS3, show both high expression trends in keloids and in elderly skin, indicating these ECMs could share similar functions in elderly and keloids skin tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the ECM composition of different ages, decellularized skin scaffolds were obtained using the decellularized method established by our group previously (Leng et al, 2020;Liu et al, 2020;Zhang et al, 2021). Especially, the decellularized skin scaffolds remained the BM structure (Figure 1A and Supplementary Figure 1A).…”
Section: Skin Proteome Profile Of Different Agesmentioning
confidence: 99%
See 1 more Smart Citation